Employee satisfaction with the built environment of a software development company. Issue 7 (1st December 2020) - da Silva, Marcelo Benetti Corrêa; Valente, Marina Giacometti; Petroli, Angela; Notari, Daniel Luis; Bebber, Suélen; Fachinelli, Ana Cristina
Abstract : Purpose: The raised competitiveness among technology companies, especially for being able to work with markets physically distant from their final consumer, makes it important to know the employee's perception about the built environment since the physical workspaces influence productivity. This paper aims to analyze the attributes and dimensions of the built environment of a development software company that most impact the employee's satisfaction through their perception. It allows the company to identify the strengths and weaknesses of the built environment, enhancing the employee's satisfaction, productivity and, consequently, the company revenues. Design/methodology/approach: This research applied a survey by the drop off method and analyzed data through confirmatory factor analysis and multiple linear regression. Therefore, these methods explain how the attributes behave in each theoretical dimension and evaluate the relation between the dependent and independent dimensions. Findings: The theoretical result of this research concerns the employee's satisfaction with the built environment of a software development company. Overall, employee satisfaction is related to the dimensions of functionality, appearance and personal relationships, not being significant aspects of configuration. On the other hand, the employee's overall satisfaction with the built environment is related to the functional dimension. Research limitations/implications: This research limitation is related to the size of the sample, which is a pre-determined and fixed population: all the company's employees. Originality/value: Perceived quality applied to a work environment of a software development company.